Water Quality Assessment at Tanggulangin Cultural Park - Ilham Putra Adiyaksa (Jurnal Sumberdaya Alam dan Lingkungan, 2022)
ABSTRACT Tanggulangin Cultural Park is a new facility provided by the local government as a recreational facility for residents. Along the way, many people use the area to boost the economy, by selling food, drinks, and so on. So it can be ascertained that water is a material that is used every day. Many residents use water from the Tanggulangin Cultural Park area for the production process of food, beverages, and other purposes, so it is necessary to know the water quality in the park, physically, chemically, and microbiologically. This research was conducted in October-November 2021 by testing the parameters of temperature, turbidity, pH, water hardness, and total coliform. The results obtained are water temperatures of 34.6 and 31.6oC, turbidity of 2.87 NTU and 3.08 NTU, pH of 7.08 and 6.92, water hardness of 1.28 mg.L-1 and 1.32 mg.L-1, and total coliforms of 7.8 CFU/100 ml and 6.8 CFU/100 ml. In general, all these parameters are still below the standard of the Regulation of the Minister of Health of the Republic of Indonesia. No. 32 of 2017. However, attention must be paid to the presence of total coliform content in water.Keywords: water quality, physical, chemical, microbiological